Application of the materials-by-design approach to armor-grade polymer-matrix composites for enhancement of ballistic-penetration resistance. Issue 1 (1st February 2016) - Grujicic, Mica; Ramaswami, S; Snipes, Jennifer; Avuthu, Vasudeva; Yen, Chian-Fong; Cheeseman, Bryan
Abstract : Purpose: – Fiber-reinforced armor-grade polymer-matrix composite materials with a superior penetration resistance are traditionally developed using legacy knowledge and trial-and-error empiricism. This approach is generally quite costly and time-consuming and, hence, new (faster and more economical) approaches are needed for the development of high-performance armor-grade composite materials. One of these new approaches is the so-called materials-by-design approach. Within this approach, extensive use is made of the computer-aided engineering (CAE) analyses and of the empirically/theoretically established functional relationships between an armor-grade composite-protected structure, the properties of the composite materials, material microstructure (as characterized at different length-scales) and the material/structure synthesis and fabrication processes. The paper aims to discuss these issues. Design/methodology/approach: – In the present work, a first step is made toward applying the materials-by-design approach to the development of the armor-grade composite materials and protective structures with superior ballistic-penetration resistance. Specifically, CAE analyses are utilized to establish functional relationships between the attributes/properties of the composite material and the penetration resistance of the associated protective structure, and to identify the combination of these properties which maximize the penetration resistance. In a follow-up paper, the materials-by-design approach will be extended to answer the questions such as what microstructural features the material must possess in order for the penetration resistance to be maximized and how such materials should be synthesized/processed. Findings: – The results obtained show that proper adjustment of the material properties results in significant improvements in the protective structure penetration resistance. Originality/value: – To the authors' knowledge, the present work is the first reported attempt to apply the materials-by-design approach to armor-grade composite materials in order to help improve their ballistic-penetration resistance.